Financial statement analysis as a tool for investment decisions and assessment of companies’ performance - Aminu Abdulrahim Olayinka (Goodwood Publishing, 2022)
Purpose: Financial Statement Analysis (FSA) and Interpretation is a vital instruments for good management decision-making in business. The main objective of this study is therefore to determine how firms could use FSA and its interpretation to aid funding and investment decisions and to avert low profitability or low investment returns. Research methodology: Data from the annual report of Nestlé Nigeria Plc are utilized for the Analysis and Interpretation of the financial ratio using descriptive statistical analytical tools for presentations. Result: The study concludes that analysis of FSs is adequate for effective decision making and that firms should pay great attention to the use of FSA to properly equip themselves with this tool and also a combination of different ratios should be used in analyzing a firm's financial performance. Proper use of FSA should be made not only in investment but also in other areas of decision-making. Limitations: The study is limited to FSs published by Nestlé Nigeria plc between the years 2014 to 2019. Contribution: The paper serves as an aid to different categories of investors when making critical investment decisions.